Mother–Daughter–Granddaughter Double GuideLiner Technique for Delivering Stents Past Multiple Extreme Angulations. (August 2016) - Finn, Matthew T.; Green, Philip; Nicholson, William; Kalra, Sanjog; Kandzari, David E.; Lembo, Nicholas; Thompson, Craig A.; Karmpaliotis, Dimitri
Abstract : Supplemental Digital Content is available in the text.